2012
DOI: 10.1016/j.outlook.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Pain and symptom management in palliative care and at end of life

Abstract: The purpose of this review is to provide a literature update of the research published since 2004 on pain and symptom management in palliative care and at end of life. Findings suggest that pain and symptom are inadequately assessed and managed even at the end of life. Although not pervasive, there is evidence of racial/ethnic disparities in symptom management in palliative care and at end of life. There is a need for a broader conceptualization and measurement of pain and symptom management as multidimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 77 publications
1
68
0
Order By: Relevance
“…This review identified themes similar to those of previous reviews on family caregivers of patients with cancer or in palliative care: inadequate knowledge and assessment skills in pain management, misunderstanding of pain medications, and poor communication with the care team. 11,20,22 However, one of the major limitations of this present review was that most of the studies included female and Caucasian family caregivers of patients with cancer from a geographic area, which limited the generalizability of the results to family caregivers with different background. As the number of hospice patients is growing and demographics of patients are changing, more studies including a representative sample will help understand this issue.…”
Section: Resultsmentioning
confidence: 95%
“…This review identified themes similar to those of previous reviews on family caregivers of patients with cancer or in palliative care: inadequate knowledge and assessment skills in pain management, misunderstanding of pain medications, and poor communication with the care team. 11,20,22 However, one of the major limitations of this present review was that most of the studies included female and Caucasian family caregivers of patients with cancer from a geographic area, which limited the generalizability of the results to family caregivers with different background. As the number of hospice patients is growing and demographics of patients are changing, more studies including a representative sample will help understand this issue.…”
Section: Resultsmentioning
confidence: 95%
“…Hospice aims to provide compassionate care to individuals facing a life‐limiting illness, such as pancreatic cancer . Hospice has been associated with improved patient functioning, decreased symptom burden, and for some, even longer survival times …”
Section: Introductionmentioning
confidence: 99%
“…[4] Moreover, pain has been positively associated with poorer quality of life [5][6][7] depression, [8,9] and greater caregiver burden. [10,11] Patient self-reporting has shown to be the best way to determine the depth and breadth of pain; [12] however, homebound patients not in immediate or constant contact with doctors and other healthcare staff often feel at a disadvantage in relation to communicating issues concerning pain.…”
Section: Introductionmentioning
confidence: 99%